Which delivery model innovations can support sustainable HIV treatment? - Bulstra, Caroline A.; Hontelez, Jan; Bärnighausen, Till (African journal of AIDS research, 2019)
The rapid scale-up of antiretroviral treatment (ART) for HIV since the mid-2000s, mostly through disease-specific or “vertical” programmes, has been a highly successful undertaking, which averted millions of deaths and prevented many new infections. However, the dynamics of the HIV epidemic and changing political and financial commitment to fight the disease will likely require new models for the delivery of ART over the coming decades if the promises of universal treatment are to be met. Delivery model innovations for ART are intended to improve both the effectiveness and efficiency of the HIV treatment cascade, reaching new people who require ART and providing ART to more people without an increase in resources. We describe twelve models for ART delivery, which could be achieved through five categories of delivery innovations: integrating ART (“vertical ART plus”, “partially-integrated ART” and “fully-integrated ART”); modifying steps in the ART value chain (“professional task-shifted ART”, “people task-shifted ART” and “technology-supported ART”); eliminating steps in the ART value chain (“immediate ART” and “less frequent ART pick-up”); changing ART locations (“private-sector ART”, “traditional-sector ART” and “ART outside the health sector”); and keeping the status quo (“vertical ART”). The different delivery model innovations are not mutually exclusive and several could be combined, such as “vertical ART plus” with “task-shifted ART”. Suitability of the models will highly depend on local and national contexts, including existing health systems resources, available funding, and type of HIV epidemic. Future implementation research needs to identify which models are the best fit for different contexts.
Gesehen am 14.01.2020